2020
DOI: 10.7717/peerj.8827
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a three-m6A related gene risk score model as a potential prognostic biomarker in clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is one of the most prevalent malignancies worldwide, N6-methyladenosine (m6A) has been shown to play important roles in regulating gene expression and phenotypes in both health and disease. Here, our purpose is to construct a m6A-regulrator-based risk score (RS) for prediction of the prognosis of ccRCC. Methods We used clinical and expression data of m6A related genes from The Cancer Genome Atlas (TCGA) dataset and the Least Absolute Shrinkage and Selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Previous studies have reported the bioinformatics analysis of total 13 m 6 A-related genes in gastric cancer ( 17 ), bladder cancer ( 18 ), and other cancers ( 19 , 20 ). In our study, a total of 19 m 6 A RNA methylation regulators were included for systematically analysis based on the recent the m 6 A review ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the bioinformatics analysis of total 13 m 6 A-related genes in gastric cancer ( 17 ), bladder cancer ( 18 ), and other cancers ( 19 , 20 ). In our study, a total of 19 m 6 A RNA methylation regulators were included for systematically analysis based on the recent the m 6 A review ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al systematically analyzed the global m6A modification pattern in KIRC and correlated it with cancerrelated gene expressions (39). Zhou (44). However, all of them have not correlated m6A regulators with TME.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of these regulators have also been analyzed in multiple malignant tumors, including liver cancer ( 45 ), gastric cancer ( 46 ), clear cell renal cell carcinoma (ccRCC) ( 47 , 48 ), colorectal cancer ( 32 ). The prognostic signature obtained using two m 6 A RNA methylation regulators (METTL14 and METTL3) had significant value in ccRCC, the AUC value for their risk prediction is 0.706 ( 47 , 48 ). The expression of METTL14 and ALKBH5 were reported to be independent prognostic factors in CRC ( 32 ).…”
Section: Discussionmentioning
confidence: 99%